Double-edged sword of desalination: Decreased growth and increased grazing endanger range-margin Fucus populations - Milec Leona J. M.; Jormalainen Veijo; Rugiu Luca; Pereyra Ricardo T.; Rothausler Eva; Havenhand Jon; De Wit Pierre R. (ELSEVIER, 2022)
Coastal ecosystems worldwide are facing intense and diverse pressures caused by anthropogenic climate change, which compromises physiological tolerance of organisms, as well as causes shifts in their biotic interactions. Within-species genetic variation plays an important role in persistence of populations under such changes by providing building blocks for adaptation. The brackish-water Baltic Sea is predicted to experience a significant desalination by the end of this century. The Baltic Sea is dominated, in terms of biomass, by a few species with locally adapted populations, making it a suitable model for studying shifting biotic interactions under changing abiotic conditions. We exposed two foundation species of brown algae, Fucus vesiculosus and Fucus radicans, to end-of-the-century projected salinity together with grazing pressure in experimental tanks. We measured growth, grazing and phlorotannin content and compared these traits between the current and projected future salinity conditions, between Fucus species, and between high and low genotypic diversity groups. Grazing, phlorotannin content and growth of both F. radicans and F. vesiculosus all showed genotypic variation. Future decreased salinity hampered growth of F. vesiculosus irrespective of genotypic diversity of the experimental population. Furthermore, the growth response to desalination showed variation among genotypes. F. radicans was more susceptible to grazing than F. vesiculosus, and, in the high genetic diversity group of the latter, grazing was higher in the future than in current salinity. Climate change induced hyposalinity will thus challenge Fucus populations at their range margins in the Baltic Sea both because of the growth deterioration and changes in grazing. Differences between the species in these responses indicate a better ability of F. radicans to cope with the changing environment. Our results emphasize the complexity of biotic interactions in mediating the climate change influences as well as the importance of genetic diversity in coping with climate change.